Intellectual Property Protection Mechanisms in Research Partnerships - Henry R. Hertzfeld; Albert N. Link; Nicholas S. Vonortas (Max Planck Institute for Research into Economic Systems, 2004)
A set of U.S.-based companies is investigated regarding the effectiveness of intellectual property protection mechanisms (IPPMs) in the formation of research partnerships. Patents are the most frequently used IPPM to protect both background and foreground knowledge in partnerships. Other IPPMs are used to protect know-how, especially in the early, forming stages of a partnership. Existing IP titles are quite useful when negotiating new partnerships. IPR negotiations are reported to be more complex in horizontal partnerships and when universities are involved.
Keywords: O31; O32; 330; Intellectual property rights; research partnerships; patents; Immaterialgüterrechte; Patent; Forschungskooperation; Unternehmenskooperation; Industrielle Forschung; USA